The Implementation Of Process Oriented Guided Inquiry Learning (Pogil) In Madrasah Ibtidaiyah - Rosadi, Ihwan (STAI MA'ARIF MAGETAN, INDONESIA, 2021)
Process Oriented Guided Inquiry Learning based learning is important to be developed in primary school because this learning method can improve students’ high level of thinking ability. This research was aimed to analyze the learning process in MI PSM Kedungputri Subdistrict Paron Distric Ngawi through implementing Process Oriented Guided Inquiry Learning. This research was used descriptive qualitative as the research design. The technique of analyzing data proposed by Miles and Huberman was used in this research, they are observation, deep interview, and questionnaire. This research was focused on the learning process, learning material, and the use of learning tools in MI PSM Kedungputri Subdistrict Paron Distric Ngawi which had not implemented Process Oriented Guided Inquiry Learning based learning. This was because the teachers had not had a guide to do the newest learning approach. This caused the learners become less interested in learning IPA and make the students’ cognitive aspects still low.